THE EFFECT OF CAREER DEVELOPMENT AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS INTERVENING VARIABLE AT THE OFFICE OF AGRICULTURE AND LIVESTOCK IN ACEH - Yusuf Iis, Em; Wahyuddin, Wahyuddin; Thoyib, Armanu; Nur Ilham, Rico; Sinta, Irada (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to examine the effect of career development and work environment on the performance of the Aceh Agriculture and Livestock Service Office employees. Data was obtained by distributing questionnaires to 100 employees. The data analysis method is Structural Equation Modeling (SEM). The results showed that career development and employee work environment had a significant effect on work motivation and employee performance. In addition, career development and work environment also have a direct effect on performance. Work motivation partially mediates the effect of career development, work environment on performance. The Department of Agriculture and Livestock is expected to improve career development in order to create a conducive work environment to improve employee performance at the Aceh Agriculture and Livestock Service Office.